Chronic immune activation and gut barrier dysfunction is associated with neuroinflammation in ART-suppressed SIV+ rhesus macaques. - Sarah J Byrnes; Kathleen Busman-Sahay; Thomas A Angelovich; Skyler Younger; Sol Taylor-Brill; Michael Nekorchuk; Stephen Bondoc; Rachel Dannay; Margaret Terry; Catherine R Cochrane; Trisha A Jenkins; Michael Roche; et al. (PLoS Pathogens)
HIV-associated neurocognitive disorders (HAND) affect ~40% of virally suppressed people with HIV (PWH), however, the precise viral dependent and independent changes to the brain are unclear. Here we characterized the CNS reservoir and immune environment of SIV-infected (SIV+) rhesus macaques during acute (n = 4), chronic (n = 12) or ART-suppressed SIV infection (n = 11). Multiplex immunofluorescence for markers of SIV infection (vRNA/vDNA) and immune activation was performed on frontal cortex and matched colon tissue. SIV+ animals contained detectable viral DNA+ cells that were not reduced in the frontal cortex or the gut by ART, supporting the presence of a stable viral reservoir in these compartments. SIV+ animals had impaired blood brain barrier (BBB) integrity and heightened levels of astrocytes or myeloid cells expressing antiviral, anti-inflammatory or oxidative stress markers which were not abrogated by ART. Neuroinflammation and BBB dysfunction correlated with measures of viremia and immune activation in the gut. Furthermore, SIV-uninfected animals with experimentally induced gut damage and colitis showed a similar immune activation profile in the frontal cortex to those of SIV-infected animals, supporting the role of chronic gut damage as an independent source of neuroinflammation. Together, these findings implicate gut-associated immune activation/damage as a significant contributor to neuroinflammation in ART-suppressed HIV/SIV infection which may drive HAND pathogenesis.